Psycho-Logic - Smedslund, Jan (Springer Berlin Heidelberg, 1988)
Psycho-Logic is an attempt to formulate explicitly the implicit common-sense psychology embedded in everyday language and taken for granted by its users. The key concepts in this system are given definitions, and the basic assumptions are presented in the form of axioms. A number of corollaries and theorems are formally proved. The text also contains numerous notes in which the formal propositions and their broader implications are discussed. It is assumed that the relationship between psycho-logic and empirical psychology is analogous to that existing between geometry and geography. Psycho-logic and geometry both provide a formal system in terms of which one may describe and analyze respectively psychological phenomena and geographical terrains. The book should be of particular interest to practicing psychologists since it provides an analysis of the main characteristics of persons and person-interactions, emphasizing such concepts as care, respect, understanding and control.